The Impact of Game-Based and Digital Interventions on Cognitive, Emotional, and Physical Health Outcomes in Older Adults: A Systematic Review - Ucik Nurmalaningsih; Joni Haryanto; Rista Fauziningtyas; Lilik Choiriyah; Basri Basri (GLOBAL HEALTH SCIENCE GROUP, 2025)
The aging population faces increasing risks of cognitive decline, depression, and reduced physical capacity. Innovative interventions such as game-based systems, experiential learning, and eHealth solutions offer promising strategies to promote healthy aging by enhancing cognitive, emotional, and physical health among older adults. Aim: This study aims to review and analyze the effectiveness of various game-based, experiential, and digital interventions on cognitive function, emotional well-being, and physical health outcomes in elderly populations. Methods: A systematic analysis was conducted on ten studies involving older adults, including randomized controlled trials, pilot studies, cohort studies, and meta-analyses. The studies investigated interventions such as cognitive games, recollection-based occupational therapy, experiential puzzle games, GAMotion, eHealth platforms, and dance-based rehabilitation. Intervention durations ranged from two sessions to twelve months, with diverse sample sizes and settings. Result:The interventions demonstrated significant improvements in cognitive functioning, reductions in depression and anxiety, enhanced physical capacity, improved quality of life, and increased social engagement. Game-based and experiential activities showed high adherence rates, suggesting good feasibility and acceptance among older adults. However, several studies were limited by small sample sizes and non-blinded assessments. Game-based, experiential, and digital interventions effectively promote cognitive, emotional, and physical well-being in older adults. These approaches are feasible, well-received, and offer valuable strategies for supporting active and healthy aging. Future research should focus on large-scale, long-term studies to confirm and extend these findings.